2018
DOI: 10.1007/s11759-018-9346-x
|View full text |Cite|
|
Sign up to set email alerts
|

Models and Metadata: The Ethics of Sharing Bioarchaeological 3D Models Online

Abstract: Digital 3D modelling is increasingly common in archaeological recording, but building the models is only part of the story. Sharing and interacting with these digital representations is essential in fostering engagement and ensuring that research is relevant to the broader community. Projects and institutions understand that much of their communication and outreach now take place via digital platforms. However, archaeologists are faced with a variety of challenges when sharing 3D models of human remains online… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…A primary reason for this seeming lack of attention relates to ethical considerations of the display of human remains. A thoughtful discussion comparing and contrasting the different positions on this issue taken by various stakeholders is well beyond the scope of this paper (though see Hassett 2018a, 2018b; Ulguim 2018). However, bioarchaeologists working in different areas of the world and in various institutions should make an effort to familiarize themselves with local cultural and political issues that they need to consider when trying to balance the often-conflicting perspectives related to research, access, and the wishes of descendant communities.…”
Section: Discussionmentioning
confidence: 99%
“…A primary reason for this seeming lack of attention relates to ethical considerations of the display of human remains. A thoughtful discussion comparing and contrasting the different positions on this issue taken by various stakeholders is well beyond the scope of this paper (though see Hassett 2018a, 2018b; Ulguim 2018). However, bioarchaeologists working in different areas of the world and in various institutions should make an effort to familiarize themselves with local cultural and political issues that they need to consider when trying to balance the often-conflicting perspectives related to research, access, and the wishes of descendant communities.…”
Section: Discussionmentioning
confidence: 99%
“…Increasingly, institutions are also understanding that much of their public engagement will now take place digitally, with platforms acting as a "medium through which information is published or exchanged" [68] though bio-archaeological data are contrasted with a critical review of current ethical and technical guidelines, indicating potentially ethically compromising practices, particularly the lack of contextualising metadata for some models [69].…”
Section: Cyber-archaeology and Bio-archaeological Issuesmentioning
confidence: 99%
“…The Antikythera mechanism is the world's first analogical computer, used by ancient Greeks to chart the movement of the sun, moon and planets, predict lunar and solar eclipses and even signal the next Olympic Games and bearing inscriptions [69] (Figure 6). The 2000-year-old astronomical calculator is a small size metal device.…”
Section: The Antikythera Mechanismmentioning
confidence: 99%
“…In both cases, clear contextualizing data with scientific justification can provide mitigation in circumstances where obtaining consent is unfeasible (Antoine 2014). However, in a recent review of bioarchaeological data shared on SketchFab, a public 3D platform, Ulguim (2018) found that many models had almost no contextualizing data: a compromising situation for the publishers and researchers working with such types of data. Furthermore, some of these 3D images had thousands of views and were available for reuse, modification and public download, meaning they could be modified, reused, or 3D printed at will.…”
Section: Sharing the Past Dead Onlinementioning
confidence: 99%
“…A new set of ethical principles can span both the investigation of digital data and the publication of digitized ancient remains. Recent guidance on the display of digital human remains notes that requirements for justification and consultation are just as applicable to the creation and sharing of imagery of human remains in a virtual setting (Ulguim 2018), and that the addition of contextualizing data is a crucial factor in mitigating ethical issues of display (Perry 2011;Williams and Atkin 2015).…”
Section: Implications For Archaeological Practicementioning
confidence: 99%